Integrated reduction/oxidation reactions and sorption processes for Cr(VI) removal from aqueous solutions using Laminaria digitata macro-algae - Dittert, Ingrid M.; Pina, Frederico; Souza, Selene M.A. Guelli U. de; Botelho, Cidália M.S.; Vilar, VÃtor J.P.; Boaventura, Rui A.R.; Souza, Antônio Augusto U. de; Silva, Eduardo A.B. da; Brandão, Heloisa de Lima (My University, 2013)
The main goal of this work was the valorization of seaweed Laminaria digitata, after acid pre-treatment, for the remediation of hexavalent chromium solutions. The Cr(VI) removal efficiency by the protonated biomass was studied as a function of different parameters, such as contact time, pH, biomass and Cr(VI) concentration, and temperature. Cr(VI) removal is based on a complex mechanism that includes a reduction of Cr(VI) to Cr(III), through the oxidation of biomass at acidic medium, and further chemical binding of Cr(III) to the negatively charged binding groups, mainly carboxylic groups. The optimum pH for chromium removal, using protonated L. digitata algae, was 2.5. The maximum amount of Cr(VI) reduction by the algae was around 2.1 mmol/g. The uptake capacity of Cr(III) by the oxidized biomass, after Cr(VI) reduction, was higher than by the algae in its original form (protonated algae). Results suggest that the oxidation of the biomass during Cr(VI) reduction, turns other active sites available for Cr(III) binding. Also, the Cr(III) binding from a solution of reduced Cr(VI) was much lower than from a pure Cr(III) solution. The result suggests the presence in solution of Cr(III) complexes with the organic matter released from the algae surface during Cr(VI) reduction. The activation energy obtained for the Cr(VI) reduction by L. digitata was 45 Â± 20 kJ mol 1. A kinetic model based on the redox reaction between Cr(VI) species and organic compounds from the biosorbent surface was able to fit well the hexavalent chromium concentration. Trivalent chromium equilibrium biosorption was well described at different chromium concentrations, considering the interaction between carboxylic groups present in the surface of the biomass and Cr(III) in solution.